Allo specchio del tempo: una nota su Asor Rosa - Mozzachiodi, Luca (L'ospite ingrato, 2021)
The essay examines the latest anthology of books and essays by the Italian critic Alberto Asor Rosa, Scritture critiche e d’invenzione, focusing on selection criteria rather than on the content of each text. Asor Rosa tries to present to the reader o coherent literary theory based on the possibility, for a classic writer, to incarnate a nation’s liveliest energies. The author than confronts the Classic with the “barbarians”: a social mass deprived of any tradition, thus very different from the people of whom he wrote in The writer and the people. A comparison is held between the numerous editions of Asor Rosa’s early works, always foreworded with different theoretical and political statements by the author, in order to show how the final version presented tends to remove considerations both on social classes and on politics.